Aktivitas Antijamur Ekstrak Etanol Daun Cengkodok (Melastoma malabathricum) Terhadap Pertumbuhan Malassezia furfur - Willy Sanjaya; Ambar Rialita; Mahyarudin Mahyarudin (Faculty of Pharmacy, Universitas Muslim Indonesia, 2021)
Pityriasis versicolor (PV) is an infection on epidermal layer of skin and the common caused by a type of yeast that live on the skin named Malassezia furfur. The increasing of fungal resistant against antifungal and high reccurence rate after cured in 2 years about 80%, requires alternative treatment that come from plants. Cengkodok leaves (Melastoma malabathricum) is used conventionally as an alternative medicine. Cengkodok leaf produces secondary metabolites which have antifungal activity. The aim of this study was to investigate the antifungal activity of ethanolic extract Melastoma malabathricum leaves (EEMML). Phytochemical screening of EEMML were performed using Thin Layer Chromatography (TLC). Melastoma malabathricum leaves were extracted with maceration method using 96% ethanol. The testing of antifungal activity was determined using disc-diffusion method with the concentration of 5; 20; 50; 100; 250; 500 ppm. Ketoconazole 10 ug/disc and Itraconazole 8ug/disc was used as positive control while negative control used 10% dimethyl sulfoxide (DMSO). EEMML didn’t showed zone of inhibition against Malassezia furfur although 100% concentration extract used. EEMML have no antifungal activity against Malassezia furfur